Assessing the factors influencing groundwater irrigation technology adoption in Ghana - Owusu V; Asante, A.V.; Pavelic, Paul (Nova Science, 2013)
Groundwater irrigation is believed to have the highest level of water control necessary for smallholder irrigation farmers to overcome household-level poverty and food insecurity. This study analyses the effects of the determinants of groundwater irrigation technology adoption with a data from 240 smallholder irrigation farmers in Ghana. The empirical results show that household size and membership of farmer-based organizations tend to have positive significant impacts on the probability of adopting groundwater manual irrigation whilst extension contacts and farm size have negative impacts. In addition the age, gender and education of the farmer, household size, access to credit, farm size and owner-cultivation tend to have significant positive effects on the probability of adopting groundwater motor pump irrigation technology whilst experience in irrigation farming and extension contacts have negative effects. The probability to adopt surface water motor pump irrigation technology is positively influenced by extension contacts and farm size whilst owner-cultivation has a negative effect. Gross margin analyses indicate higher gross margins for groundwater motor pump irrigators. To promote the groundwater irrigation technology adoption, the update of skills and knowledge of the farmers on the existing irrigation technologies must be facilitated through frequent participation in workshops and training programs on irrigation. Smallholder irrigation farmers must be supported with accessible micro-credit facilities for acquisition of low-cost irrigation pumps.